The Strategies and Assignment of Teaching and Learning of Speaking Ability in an Educational Institution - A Fawazien Ready (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
This research is conducted to describe the implementation of teaching and learning strategies and the assignment of innovative speaking ability for formal school. The research method used in this study is qualitative research with library research. The learning strategies for the students may consist of direct and indirect method. The teaching strategies can be a part of the activities available done in the class, such as; role plays, simulation, telling story, interview, conversation, discussion, and using the target language outside the classroom. The assignment form of speaking ability may be grouped as; Imitative Speaking (word repetition task and phone pass test), Intensive Speaking (directed response test and read-aloud test), responsive speaking (question and answer and giving interaction and direction), interactive speaking (interview and discussion conversation), and extensive speaking (oral presentation and retelling story and news)